(untitled) (Research, Society and Development, 2021)
Breast neoplasm, and the superiority in incidence and, above all, for its psychosocial effects, becomes the most fearful in the female sex. Objetivo: Realizar uma revisão de literatura sobre o cuidado de enfermagem nas mulheres pós mastectomia. Methodology: Narrative literature review study selected 101 articles and we used 22, for the development of the study in the period between October 2018 and May 2019. Results: The multidisciplinary team, where they encompass a diversity of professionals, turning to the aspects of humanization of care. The emotional aspects of the patient and family should be seen in a special way, where the oncology unit is a stressful and exhausting environment in which the support of the nursing team is essential to ease the existing conflicts. Conclusion: However, it was observed the fundamental importance of the health care unit’s involvement, as a whole, in material and personal aspects, in the reception and continuing education, in the way patients are conducted in unexpected events or incidents, which are common in care environments, and in the care of oncologic patients, considering it necessary to humanize care.